Metroseksualizm - Gębala, Przemysław (Horyzonty Wychowania, 2017)
The conception of masculinity, the same as femininity, is always in process. Neither masculinity nor femininity is perfectly and forever shaped in culture and society. I would say it is a two faceted process, a reciprocal discourse between women and men in culture, which I would call the process of negotiation between men and women. This is very sensitive to environmental context, especially any kind of social changes and movements. Therefore the approach to the topic of masculinity demands to have a broader view of the processes of culture, social, economical, technological and political issues.